1999
DOI: 10.1097/00007632-199902150-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Coralline Hydroxyapatite With Bone Marrow, Autogenous Bone Graft, or Osteoinductive Bone Protein Extract for Posterolateral Lumbar Spine Fusion

Abstract: These data indicate that coralline hydroxyapatite with bone marrow was not an acceptable bone graft substitute for posterolateral spine fusion. When combined with autogenous iliac crest bone graft-coralline hydroxyapatite served as a graft extender yielding results comparable to those obtained with autograft alone. Coralline hydroxyapatite served as an excellent carrier for the bovine osteoinductive bone protein extract yielding superior results to those obtained with autograft or bone marrow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(92 citation statements)
references
References 34 publications
3
84
0
5
Order By: Relevance
“…52 In single-level posterolateral lumbar arthrodesis performed in 48 adult New Zealand White rabbits, the combination of BMPs and coralline hydroxyapatite resulted in 100% fusion rates. 53 This was in contrast to the groups receiving coralline hydroxyapatite with bone marrow (0% union rates) and the coralline hydroxyapatite with autogenous iliac crest bone (50% union rates). The authors concluded that when coralline grafts were combined with autogenous iliac crest bone graft served as a graft extender yielding results comparable to those obtained with autograft alone.…”
Section: Animal Studiesmentioning
confidence: 82%
See 1 more Smart Citation
“…52 In single-level posterolateral lumbar arthrodesis performed in 48 adult New Zealand White rabbits, the combination of BMPs and coralline hydroxyapatite resulted in 100% fusion rates. 53 This was in contrast to the groups receiving coralline hydroxyapatite with bone marrow (0% union rates) and the coralline hydroxyapatite with autogenous iliac crest bone (50% union rates). The authors concluded that when coralline grafts were combined with autogenous iliac crest bone graft served as a graft extender yielding results comparable to those obtained with autograft alone.…”
Section: Animal Studiesmentioning
confidence: 82%
“…The authors concluded that when coralline grafts were combined with autogenous iliac crest bone graft served as a graft extender yielding results comparable to those obtained with autograft alone. 53 In addition to BMPs other molecules have been investigated. In a comparative study of Insulin growth factor-1 (IGF-1) and BMP-2, IGF-1 was more potent inducer of bone regeneration when loaded on a coralline hydroxyapatite scaffold for the treatment of proximal tibial defects.…”
Section: Animal Studiesmentioning
confidence: 99%
“…The well-reported model developed by Boden was used in this study [2]. This model provides an excellent preclinical evaluation of materials for spinal fusion and its usefulness is reflected in its wide acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Single-level posterolateral lumbar fusion was performed at L5-L6 in 69 adult New Zealand white rabbits as reported and developed by Dr. Boden et al [2] following institutional ethical approval. The study design is outlined in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Data from animal studies would suggest that a bone graft substitute with some level of osteoinductivity is most effective for posterolateral spinal arthrodesis because it can combine the creeping substitution process of bone ingrowth from the decorticated host bone, with recruitment and differentiation of additional progenitor cells from the surrounding soft tissue adding a centripetal pattern of bone-healing 5,6 . Specific BMPs (BMP-2, 4, 6, 7, and 9) have demonstrated the potential for varying degrees of osteoinductivity 7 .…”
Section: Current Status Of Osteoinductive Agents For Spine Fusionmentioning
confidence: 99%